Design and costing of a packed bed thermal energy storage system - Khan, Mu-een (Stellenbosch : Stellenbosch University, 2025)
Khan, M. 2025. Design and costing of a packed bed thermal energy storage system. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/8a3d14ed-a0ca-4752-834e-ba899287e0c2